Interactions between local and migrant workers at the workplace - Gil Epstein; Yosef Mealem (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
In this paper we consider the interaction between local workers and migrants in the production process of a firm. Both local workers and migrants can invest effort in assimilation activities in order to increase the assimilation of the migrants into the firm and so by increase their interaction and production activities. We consider the effect, the relative size (in the firm) of each group and the cost of activities, has on the assimilation process of the migrants.
Keywords: D74; F23; I20; J61; L14; 330; Assimilation; Contracts; Ethnicity; Market Structure; Networks; harassment